Effect of SeO2 on glass coloration from silver nanoparticles in self striking process. (2017) - Sangwaranatee, N.; Kaewkhao, J.; Ruangtaweep, Y.
Abstract: In this work, the effect of selenium oxide on glass coloration from silver nanoparticles (AgNPs) doped in glasses were investigated. The glass samples were prepared with glass composition (63.97-x(SiO2 : 10CaO: 10K2 O: 15Na2 O: 0.5Sb2 O3 : 0.5SnO2 : 0.03AgNPs: xSeO2 (where x= 0.0, 0.1, 0.2, 0.3, 0.4, and 0.5% by weight). The glasses were melted by conventional melt quench technique at 1, 500 °C in open atmosphere. The results were found that, the glass samples doped with SeO2 concentration of 0.1 to 0.5% by weight showed the amber color. The color was confirmed by UV-visible spectrophotometer in the wavelength range 200-1, 100 nm and from the color coordinate in CIE L∗a∗b∗ system. Moreover, the amber color was obtained immediately when take out the glass from the furnace, without second heat treatment.